Evaluasi Penerapan Keselamatan dan Kesehatan Kerja Pada Penambangan Batubara CV. Air Mata Emas, Desa Tumpuk Tengah , Kecamatan Talawi, Kota Sawahlunto, Provinsi Sumatera Barat. - asnel muhammad; fadhilah fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
CV.Airmata Emas is a company engaged in coal mining with underground mining (room and pillar) and has great risks and dangers, it is necessary to apply occupational safety and health management by working according to SOPs and JSAs that have been companies that have set. Hazards and risks can occur during buffering and lorry operation activities, it is necessary to carry out a risk analysis for data on potential hazards, then weighting to determine the appropriate control method according to the conditions. To get the value of each risk as well as the implementation of Occupational Safety and Health and the application of JSA and Occupational Safety and Health SOPs obtained using questionnaires, interviews, and observations of work activities. The results showed that the questionnaire regarding Occupational Safety and Health (K3) on knowledge with a value of 75.33, on attitudes with a value of 83.73, and on actions with a value of 79.82. JSA and SOP have been applied in mining activities. Based on the results of the questionnaire, the JSA value was 67.33 and the SOP was 68. Risk analysis using the questionnaire results obtained that the risk that often occurs in the buffering process is slipping and falling because the road is slippery and occurs when measuring the place where the support wood will be installed in the hole that The risk level is L (Low) with a proportion of 25%, falling on broken and weathered support wood on the walls and roof of the hole when transporting the supporting wood from the lorry to the front work using a handcart, the risk level L (Low) is obtained with a percentage of 5 %, fell on the supporting wood on the wall and roof of the hole when installing the supporting connector (paran) which obtained a risk level of L (Low) with a percentage of 5%. The risk that often occurs in the process of operating the lorry is falling and slipping when carrying out an inspection at the workplace which has a risk level of L (Low) with a percentage of 40%. Control using control methods (hierarchy of control) namely elimination, substitution, Engineering Control, Administration Control, and PPE.